Etiology of pancytopenia with reference to bone marrow biopsy in a tertiary care hospital: A hospital-based study - Aparna Dutta; Harbamon Engti; Asha Borah; Padmashri Ronghangpi; Adity Sharma; Mrigen Choudhury (Asian Journal of Medical Sciences, 2024)
Background: Pancytopenia is a common hematological entity and a striking feature of many life-threatening illnesses. Aims and Objectives: The study was conducted to identify the etiology of pancytopenia. (i) To find out primary bone marrow (BM) causes of pancytopenia. (ii) To evaluate the spectrum of BM morphology in pancytopenia cases. Materials and Methods: This hospital-based observational study was conducted between June 2021 and May 2022 in a tertiary care hospital in Dibrugarh in all pancytopenia cases of age above 12 years and meeting the inclusion criteria. After taking written consent, detailed history, clinical examination, and baseline investigations were done followed by BM examination. Results: Mean age was 45.39±15.49 years. Majority were males 41 (56.9%) and 31 (43.1%) were females. The most common cause of pancytopenia was Megaloblastic anemia (30.5%) cases, followed by aplastic anemia (18%) and myelodysplastic syndromes (16.7%). About 72 (100%) had pallor followed by weakness (86.1%), bleeding tendencies (70.8%), and fever (52.8%). Conclusion: The study underscores the critical role of BM biopsy in the diagnostic workup of pancytopenia. It confirms that BM biopsy is indispensable for identifying the diverse etiologies of pancytopenia and in implementing the appropriate therapy.